Ear Advantage for Musical Location and Relative Pitch: Effects of Musical Training and Attention. (June 2017) - Hutchison, Joanna L.; Hubbard, Timothy L.; Hubbard, Nicholas A.; Rypma, Bart
Trained musicians have been found to exhibit a right-ear advantage for high tones and a left-ear advantage for low tones. We investigated whether this right/high, left/low pattern of musical processing advantage exists in listeners who had varying levels of musical experience, and whether such a pattern might be modulated by attentional strategy. A dichotic listening paradigm was used in which different melodic sequences were presented to each ear, and listeners attended to (a) the left ear or the right ear or (b) the higher pitched tones or the lower pitched tones. Listeners judged whether tone-to-tone transitions within each melodic sequence moved upward or downward in pitch. Only musically experienced listeners could adequately judge the direction of successive pitch transitions when attending to a specific ear; however, all listeners could judge the direction of successive pitch transitions within a high-tone stream or a low-tone stream. Overall, listeners exhibited greater accuracy when attending to relatively higher pitches, but there was no evidence to support a right/high, left/low bias. Results were consistent with effects of attentional strategy rather than an ear advantage for high or low tones. Implications for a potential performer/audience paradox in listening space are considered.